Simultaneous determination of difenoconazole, trifloxystrobin and its metabolite trifloxystrobin acid residues in watermelon under field conditions by GC–MS/MS. (8th May 2017) - Kang, Di; Zhang, Haizhen; Chen, Yuling; Wang, Fei; Shi, Lihong; Hu, Deyu; Zhang, Kankan
Abstract: An optimized quick, easy, cheap, effective, rugged and safe method for the simultaneous determination of difenoconazole, trifloxystrobin and its metabolite trifloxystrobin acid residues in watermelon and soil was developed and validated by gas chromatography with tandem mass spectrometry. The samples were extracted with acetonitrile (1% formic acid) and cleaned up by dispersive solid‐phase extraction with octadecylsilane sorbent. The limit of quantification of the method was 0.01 mg/kg, and the limit of detection was 0.003 mg/kg for all three analytes. The recoveries of the fungicides in watermelon, pulp and soil were 72.32–99.20% for difenoconazole, 74.68–87.72% for trifloxystrobin and 78.59–92.66% for trifloxystrobin acid with relative standard deviations of 1.34–14.04%. The dissipation dynamics of difenoconazole and trifloxystrobin in watermelon and soil followed the first‐order kinetics with half‐lives of 3.2–8.8 days in both locations. The final residue levels of difenoconazole and trifloxystrobin were below 0.1 mg/kg (maximum residue level [MRL] set by China) and 0.2 mg/kg (MRL set by European Union), respectively, in pulp samples collected 14 days after the last application. These results could help Chinese authorities to establish MRL of trifloxystrobin in watermelon and provide guidance for the safe and proper application of both fungicides on watermelon.